THE DESIGN AND USE OF PERFORMANCE INFORMATION IN INDONESIAN LOCAL GOVERNMENTS UNDER DIVERGING STAKEHOLDER PRESSURES. (26th March 2012) - Mimba, Ni Putu S. H.; van, G. Jan; Tillema, Sandra
SUMMARY Public sector managers in less developed countries are confronted with opposing forces. A lack of sufficient resources along with a tradition of corruption are obstacles for developing and using performance measurement systems. However, recent public sector reforms in less developed countries, including decentralisation and anti‐corruption programmes, stimulate the development and use of such systems. On the basis of a framework, which distinguishes different types of stakeholders, each with particular performance interests, we analyse how public sector managers are coping with the two opposing forces, given the relative power positions and the interests of their stakeholders. On the basis of four cases studies of local government agencies in Bali (Indonesia), we found that with respect to the annual performance reports, managers in these agencies focus more on fulfilling the formal requirements regarding the format of these reports and on their timely submission than on their contents, which are all symptoms of a symbolic rather than functional use of performance information. However, the reports include information on inputs that is linked to similar information in short‐term reports, which the managers use in a functional manner. These managers show a kind of juggling behaviour, in the sense that they partially try to serve conflicting performance interests. Copyright © 2012 John Wiley & Sons, Ltd.